DEVELOPMENT OF LINGUISTIC SKILLS IN BHAKTI LITERATURE - Singh, Jugendra; Yadav, Soniya (ShodhKosh: Journal of Visual and Performing Arts, 2024)
To understand the developmental nature of linguistic skills in Bhakti literature, it is necessary to understand the medieval period. In the present perspective, Bhakti period poetry is achievable from both the perspective of eternality and relevance of devotion. Linguistic richness, comprehensiveness and excellence are the biggest contribution of Bhakti period. From the perspective of language, Sanskrit, Persian and Hindi languages ​​have dominated Bhakti literature. Clearly, Indian culture, religion, ethics and thoughts were proclaimed through the compositions of Awadhi and Brajbhasha in Bhakti literature. Hindi Bhakti literature flourished more under the patronage of Hindu rulers. In Indian society, Bhakti period poets left an unprecedented mark of their compositions through singing. It is called the golden age of Hindi literature from both the perspectives of quality and quantity of language in the compositions of Bhakti literature. Bhakti period poetry is the first to define individual character and identity in the languages ​​of India. The elevation of human values, the source of knowledge of modernity, the emphasis on women’s consciousness and artistic beauty make the poetry timeless. From the point of view of preservation of human values, the development of skills like song-music, story-screenplay, translation, editing and language communication is included in Bhakti literature.